1990
DOI: 10.1037/0022-3514.59.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Motivated recruitment of autobiographical memories.

Abstract: We hypothesized that people motivated to believe that they possess a given trait search for autobiographical memories that reflect that trait, so as to justify their desired self-view. We led subjects to believe that either extraversion or introversion was desirable, and obtained convergent evidence from open-ended memory-listing tasks as well as from reaction-time tasks measuring the speed with which memories could be generated that this manipulation enhanced the accessibility of memories reflecting the desir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
280
0
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 324 publications
(306 citation statements)
references
References 31 publications
22
280
0
4
Order By: Relevance
“…First, by showing that our findings extended to the domain of memory, we contribute to the limited existing research on motivated memory biases, adding equalitymotives to a short list of social-psychological motivations known to influence the information individuals remember (see also Hennes et al, under review;Story, 1988;Sanitioso, Kunda, & Fong, 1990). Second, the empirical paradigm itself has advantages that may be of use to other researchers.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…First, by showing that our findings extended to the domain of memory, we contribute to the limited existing research on motivated memory biases, adding equalitymotives to a short list of social-psychological motivations known to influence the information individuals remember (see also Hennes et al, under review;Story, 1988;Sanitioso, Kunda, & Fong, 1990). Second, the empirical paradigm itself has advantages that may be of use to other researchers.…”
Section: Discussionmentioning
confidence: 67%
“…Documenting effects of motivated cognition on memory, recent work showed that individuals motivated to deny climate change were more likely to recall information in an article or video describing human contributions to climate change in system-exonerating Story, 1988;Sanitioso, Kunda, & Fong, 1990). …”
Section: Evidence For Motivated Cognitionmentioning
confidence: 99%
“…Support for this interpretation comes from studies in which tendencies to bask in reflected glory or to engage in self-enhancing downward comparison were increased by procedures, such as failing at an ego-involving task or learning that one possesses undesirable personality traits, that temporarily lowered subjects' self-esteem (e.g., Cialdini & Richardson, 1980;Crocker, Thompson, McGraw, & Ingerman, 1987). Further support comes from studies in which subjects are shown to be biased toward embracing, as self-descriptive, whichever of two opposing traits (extraversion or introversion) is presented as being predictive of personal success (Kunda & Sanitioso, 1989;Sanitioso, Kunda, & Fong, 1990).…”
Section: Second-order Implicit Self-esteem Effectsmentioning
confidence: 99%
“…the 10 commandments; Aristotle, Nicomachean Ethics). Consequently, morality is central for both the private and the public self (Chaiken, Giner-Sorolla, & Chen, 1996;Greenwald, 1980;Sanitioso, Kunda, & Fong, 1990). Third, exposing ethical failure is associated with embarrassment, shame, or guilt and might further extend to tangible losses such as fines, forced resignation, and even time behind bars.…”
Section: Ethical Dissonance and Cognitive Dissonancementioning
confidence: 99%
“…Moral values are a central component of a person's positive self-image (Chaiken, Giner-Sorolla, & Chen, 1996). People desire to perceive themselves as honest and deserving, and strongly believe in their own morality (Greenwald 1980;Sanitioso, Kunda, & Fong, 1990). For instance, about 84% of the respondents in a study with large samples of adolescents, university students, and adults reported being moral and considered their morality to be central to their private and public identities (Aquino & Reed, 2002).…”
mentioning
confidence: 99%